MAKNA BEKERJA DAN SPIRIT KEWIRAUSAHAAN DALAM PERSPEKTIF Q.S AN’AM AYAT 135 - Nurkamidien, Syukrin; Waliko, Waliko; Tsaqib, Muhammad Najmu (DAS Institute, 2022)
This study aims to explain the meaning of work and the spirit of entrepreneurship in Islamic perception, especially in Q.S An-Na'am verse 135. This study uses a qualitative-thematic approach and collects library research data. The study results show that the two interpretations of Ahmad Musthofa al Maraghi in his Tafsir al Maraghi and Prof. Wahbah az Zuhaili in his Tafsir al Munir provide interpretations of Q.S al An'am verse 135 so that Muslims are enthusiastic about working and entrepreneurship. Of course, the job is lawful and follows the provisions of syara'. Because good work will produce good results, whether in this world or the hereafter. But on the contrary, if the work is terrible, then it will produce bad thinks too.